Detection of gas molecules by means of spectrometric and spectroscopic methods - Blohm, Annika; Sieburg, Anne; Popp, Jürgen; Frosch, Torsten (Elsevier, 2019)
In this chapter, several spectroscopic and spectrometric techniques applied in environmental gas analysis are presented. Focus is placed on the underlying mechanisms in analysis and instrumentation. Advantages and limitations of all techniques are thoroughly discussed. Mass spectrometric techniques, ion-mobility spectroscopy and laser spectroscopic methods including several IR spectroscopic, absorption, and fluorescence methods as well as Raman spectroscopy are covered to give the reader a good overview of currently available and established techniques for environmental gas analysis.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Absorption spectroscopy; Enhancement methods; Environmental gas analysis; Fluorescence; GHGs; IMS; Laser spectroscopy; Mass spectrometry; Raman spectroscopy; VOCs